2015
DOI: 10.33301/2015.17.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Using the Spatial Econometric Approach to Analyze Convergence of Labor Productivity at the Provincial Level in Vietnam

Abstract: This paper employs the spatial econometric approach to undertake a research of labor productivity convergence of the industrial sector among sixty provinces in Vietnam in the period 1998-2011. It is shown that the assumption of the independence among spatial units (provinces in this case) is unrealistic, being in contrast to the evidence of the data reflecting the spatial interaction and the existence of spatial lag and errors. Therefore, neglecting the spatial nature of data can lead to a misspecification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The authors also found that the productivity growth rates of industry, agriculture, and services sectors are 6.3%, 1.6%, and -4.7%, respectively. In a recent analysis, Nguyen et al (2015) applied a spatial econometric approach to investigate the dynamics of industrial labor productivity among 60 provinces over the period 1998-2011. The result showed that the spatial dependance among regions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also found that the productivity growth rates of industry, agriculture, and services sectors are 6.3%, 1.6%, and -4.7%, respectively. In a recent analysis, Nguyen et al (2015) applied a spatial econometric approach to investigate the dynamics of industrial labor productivity among 60 provinces over the period 1998-2011. The result showed that the spatial dependance among regions, i.e.…”
Section: Introductionmentioning
confidence: 99%